How team safety stressors affect proactive and prosocial safety behaviors: Felt safety responsibility and affective commitment as mediators - Wang, Dan; Sheng, Zitong; Wang, Xueqing; Griffin, Mark; Zhang, Yiting; Wang, Ziying (Elsevier, 2021)
Although research has thoroughly established that employees’ safety citizenship behaviors (SCBs) are critical to workplace safety, less is known about the patterns by which team-level safety stressors affect SCBs. Extending work stress theories to the team level, this study employs a multilevel model and aims to assess two unique mediating mechanisms, felt safety responsibility and affective commitment, through which team safety stressors influence proactive and prosocial safety behaviors respectively. Data were collected from 408 construction workers and their supervisors from 28 project teams in China. Results showed that team safety stressors significantly and negatively predicted both types of SCB. Moreover, felt safety responsibility mediated the relationship between team safety stressors and proactive safety behavior, and affective commitment mediated the relationship between team safety stressors and prosocial safety behavior. This study contributes to workplace safety research by highlighting the important role of team safety stressors in predicting SCBs and different mediating mechanisms for the two types of SCB. Based on our findings, practical interventions aiming at improving workplace safety could be targeted at training managers to provide a supportive work environment where safety roles are clearly and consistently communicated, as well as to attend to potential interpersonal conflicts within the work team. These strategies will encourage more SCBs by promoting workers’ understanding of their responsibilities and enhancing their commitment to the organization.